REACTIONS AND REACTION RATES IN THE REGIONAL AQUIFER BENEATH THE PAJARITO PLATEAU, NORTH-CENTRAL NEW MEXICO, USA - Hereford A.G.; Keating E.H.; Guthrie G.D.; Zhu Ch. (My University, 2007)
Reactions and reaction rates within aquifers are fundamental components of critical hydrological processes. However, reactions simulated in laboratory experiments typically demonstrate rates that are much faster than those observed in the field. Therefore, it is necessary to conduct more reaction rate analyses in natural settings. This study of geochemical reactions in the regional aquifer in the Pajarito Plateau near Los Alamos, New Mexico combines modeling with petrographic assessment to further knowledge and understanding of complex natural hydrologic systems. Groundwater geochemistry shows marked evolution along assumed flow paths. The flow path chosen for this study was evaluated using inverse mass balance modeling to calculate the mass transfer. X-ray diffraction and field emission gun scanning electron microscopy were used to identify possible reactants and products. Considering the mineralogy of the aquifer and saturation indices for the regional water refined initial interpretations. Calculations yielded dissolution rates for plagioclase on the order of 10−15 mol s−1 m−2 and for K-feldspar on the order of 10−17 mol s−1 m−2, orders of magnitude slower than laboratory rates. While these rates agree with other aquifer studies, they must be considered in the light of the uncertainty associated with geometric surface area estimates, 14C ages, and aquifer properties.
Keywords: FELDSPAR; INVERSE MASS BALANCE MODELING; USA; GEOCHEMISTRY; KINETICS